2018
DOI: 10.4236/tel.2018.815221
|View full text |Cite
|
Sign up to set email alerts
|

Revalidating Saving-Investment Comovement in Nigeria: Surprises, Stylized Facts and Explanations

Abstract: Numerous studies have attempted to examine the relationship between savings and investment without a consensus conclusion. Interestingly, there have been profound findings, arguments and scholarly contributions on the subject by different authors, researchers and scholars from most first class institutions around the world. To further heighten the argument around the subject, Feldstein-Horioka in his hypothesis, after running many regression, suggests that saving-investment co-movement under perfect capital mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…Slimane, Tahar, and Essid (2013) employed the Engel and Granger cointegration procedure for Tunisia and Morocco where the significantly different from zero and negative ECT indicate the adjustment speed of investment and savings ratios in the long run. Similar results are reported in Mitra (2017) for South Africa and Joseph and Shobande (2018) for Nigeria. The values of ECT in previous studies, which are estimated by employing different cointegration procedures, provide results of lower value of the ECT compared to this study.…”
Section: Empirical Findingssupporting
confidence: 89%
“…Slimane, Tahar, and Essid (2013) employed the Engel and Granger cointegration procedure for Tunisia and Morocco where the significantly different from zero and negative ECT indicate the adjustment speed of investment and savings ratios in the long run. Similar results are reported in Mitra (2017) for South Africa and Joseph and Shobande (2018) for Nigeria. The values of ECT in previous studies, which are estimated by employing different cointegration procedures, provide results of lower value of the ECT compared to this study.…”
Section: Empirical Findingssupporting
confidence: 89%
“…Thus, it is unclear whether access to finance can help these two countries better reposition their resources. Secondly, studies have shown that access to finance is important to escape the vicious cycle of poverty for countries rich in resources and to address their socioeconomic woes [16,28,29]. For example, oil exploration has turned Nigeria's agricultural society into an oil-producing oil nation, but not without infrastructural deficits or slow socioeconomic development.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, access and use of financial services have not only become paramount but also the hallmark of various campaigns among stakeholders and scholars. While the peculiarity of savings is critical, literature agreed that both savings and investment are share of income, but less agreement exist on whether savings and investment are really equal at equilibrium (Joseph & Shobande, 2018).…”
Section: Overviewmentioning
confidence: 99%